Case Report: Surgical androgen deprivation therapy for prostate cancer in a patient with concurrent scrotal paget’s disease - Yang, Sinan; Wang, Qiao; Shi, Yuanlong; Peng, Bo; Yang, Jinye; Luo, Zongyan; Li, Can; Xu, Jian; Luo, Wei; Bi, Chengwei; Zhao, Bin; Yang, Yong (Frontiers in Oncology, 2025)
IntroductionProstate cancer (PCa) and Scrotal Paget’s disease (SPD) are two distinct malignancies, and reports of their concurrent occurrence are very limited. The aim of this case was to discuss the individualized treatment strategy for an elderly patient with metastatic PCa combined with SPD.Case presentationAn octogenarian male (aged 88 years) with metastatic PCa (Gleason 8 = 4 + 4, bone metastases, suspected lung involvement) received androgen deprivation therapy (ADT: bicalutamide + goserelin), achieving biochemical control (PSA <0.1 ng/mL; testosterone <20 ng/dL) over three years (2020-2023). In September 2023, he developed a painless scrotal nodule (0.5 cm), which progressed to a 3 cm ulcerated lesion with pruritus and bleeding by December 2023. Histopathology confirmed SPD. After multidisciplinary review and family prioritization of symptom relief, wide local excision (3-cm margins) and bilateral orchiectomy were performed on December 9, 2023. Postoperative pathology confirmed a primary SPD (CK7+/GCDFP-15+). Postoperative recovery was uncomplicated, and no recurrence was observed at the one-year follow-up in December 2024.Clinical discussionDual pathology requires a multimodal approach. Surgery can control symptoms, simplify ADT, and reduce the risk of SPD recurrence. This decision requires balancing tumor efficacy, age, and quality of life (QoL).ConclusionCombined surgical resection and ADT may benefit older patients with synchronous PCa and SPD(CK7+/GCDFP-15+), but patient selection and informed consent remain critical.